2016
DOI: 10.1158/0008-5472.can-15-0642
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Intratumoral Heterogeneity of Breast Cancer by Multiparametric In Vivo Imaging: A Translational Study

Abstract: Differential diagnosis and therapy of heterogeneous breast tumors poses a major clinical challenge. To address the need for a comprehensive, non-invasive strategy to define the molecular and functional profiles of tumors in vivo, we investigated a novel combination of metabolic positron emission tomography (PET) and diffusion-weighted (DW) magnetic resonance imaging (MRI) in the polyoma virus middle T transgenic mouse model of breast cancer. The implementation of a voxelwise analysis for the clustering of intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…It is suggested that FDG-PETby means of standardized uptake value (SUV) and DWIexpressed as apparent diffusion coefficient (ADC)correlate weakly, but with a statistically significant negative correlation on a voxel level within tumors of individual patients [3,4]. The voxelwise combination of SUV and ADC may further be used to identify tissue classes within the tumor by joint statistical modelling [5][6][7][8][9]. With the introduction of integrated PET/MR, it has become possible to acquire PET and DWI simultaneously, thereby potentially improving image coregistration.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that FDG-PETby means of standardized uptake value (SUV) and DWIexpressed as apparent diffusion coefficient (ADC)correlate weakly, but with a statistically significant negative correlation on a voxel level within tumors of individual patients [3,4]. The voxelwise combination of SUV and ADC may further be used to identify tissue classes within the tumor by joint statistical modelling [5][6][7][8][9]. With the introduction of integrated PET/MR, it has become possible to acquire PET and DWI simultaneously, thereby potentially improving image coregistration.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term survivors had a predominant tumor habitat with high Cancer December 15, 2018 enhancement and intermediate cell density, whereas the tumors of short-term survivors had habitats with low enhancement and high FLAIR signals (indicating necrosis). 194 More recently, these same authors presented a computational framework with which to quantitatively extract image features from the tumor habitats that demonstrated high accuracy to potentially predict the survival of patients with glioblastoma.…”
Section: Habitat Imagingmentioning
confidence: 99%
“…These subregions were validated with coregistered hematoxylin and eosin staining and ex vivo autoradiography in a preclinical setting. 194…”
Section: Habitat Imagingmentioning
confidence: 99%
“…This requires new methodological approaches towards the combination of multi-parametric image features (aka Bradiomics^) and multi-omics data from tissue or liquid biopsies so as to yield clinically relevant information. Here, artificial intelligence-based approaches have been proposed as one way to derive predictive biomarkers for therapeutic responses in cancer [45,46].…”
Section: Future Challengesmentioning
confidence: 99%